IMPLEMENTASI GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN MATEMATIKA DI ERA 4.0 - Sembiring, Thresia Yohana; Purba, Ricky Rikardo; Silangit, Menna Sri Ulina; Manik, Efron; Hutauruk, Agusmanto J.B (JURNAL CURERE, 2023)
Geogebra is one of the applicative software that can be used as a learning medium for mathematics in the 4.0 era. This application can help teachers in creating learning media especially in the geometry material as well as geogebra can facilitate mathematical teacher in making graphical illustrations and geometric designs so that it is expected to arouse the spirit of students in learning math. The method used in this research is a literature review. The purpose of this research is (1) to explain the definition of geogebra; (2) to demonstrate the use of Geogebra as a learning medium in improving the ability of teachers in teaching mathematics in the era 4.0. The result of this study is that geogebra is a dynamic and interactive program that allows for a lot of exploration of a mathematical concept especially on the material of geometry transformation.